Governance Mechanisms and Earnings Integrity: The Impact of Board and Audit Committee Independence on Real Earnings Management - Sulieman, Mohammad Tayseer; Rashid, Norfadzilah; Dakhlallh, Mohammad Mustafa (Journal of Ecohumanism, 2024)
The current study aimed to examine the effect of the independence both of the board of directors and audit committee for non-financial companies in Jordan. To show that effect, we used aggregated real earnings management (REM_ALL) and cash flow from operations (CFO), discretionary expenditure (DISX), and production cost (PROD) as proxies of real earnings management. The current study covered 740 firm-year observations for industrial and services firms listed in Amman Stock Exchange (ASE) during the period from 2012 to 2021. Using the Fixed Effect approach, the results showed that the board's independence has a positive effect on aggregated real earnings management (REM_ALL) and production cost (PROD), and a negative effect on cash flow from operations (CFO) and discretionary expenditure (DISX). While the study results indicated that the audit committee independence has a negative effect on aggregated real earnings management (REM_ALL) and cash flow from operations (CFO), and production cost (PROD), but a positive effect on discretionary expenditure (DISX). Further, for the control variables, the results showed that the firm size (FSIZE) has an insignificant effect on all model variants of real earnings management (REM). Meanwhile, financial leverage (LEV) has a negative effect on all model variants of real earnings management (REM). Thus, these findings provide shreds of evidence for all the regulators, investors, and executives in Jordan into account when designing corporate regulations. Hence, due to the significant impact on public policies, the results should be of interest to the regulators and standard setters.